Integration of Thought and Action: Arm Weights Facilitate Search Accuracy in 24‐Month‐Old Children. (8th September 2017) - Arterberry, Martha E.; Hespos, Susan J.; Herth, Rachel A.
Abstract : Search errors are common in cognitive tasks with infants and toddlers, and these errors reveal important insights to the development of competence and performance. Rivière and Lécuyer (2008, Journal of Experimental Child Psychology, 100, 1) demonstrated that 29‐month‐olds typically make an error during a search task involving invisible displacement. However, performance improves significantly when children wear weighted wrist bands while doing the task. To investigate this phenomenon further, we tested 24‐month‐old children in an identical search task ( N  =   35). Half the children wore weighted wrist bands, and the rest were in a no‐weight condition. To test how far this phenomenon generalizes, we also tested the same children in a second search task where they needed to find a ball that had rolled behind one of four doors. The results showed that children in the no‐weight condition replicated previous findings of poor performance on both search tasks. Unlike 29‐month‐olds, the 24‐month‐olds in the weighted condition did not immediately show improvement on the search tasks. However, after an initial search attempt, children wearing weights performed significantly better than chance. The findings shed new light on the interplay between thought and action.